2022
DOI: 10.1021/acs.jafc.2c04079
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Genome Mining with an OSMAC Approach Facilitates the Discovery of and Contributions to the Biosynthesis of Melleolides from the Basidiomycete Armillaria tabescens

Abstract: Genome mining revealed that the genomes of basidiomycetes may include a considerable number of biosynthetic gene clusters (BGCs), yet numerous clusters remain unidentified. Herein, we report a combination of genome mining with an OSMAC (one strain, many compounds) approach to characterize the spectrum of melleolides produced by Armillaria tabescens CPCC 401429. Using F1 fermentation medium, the metabolic pathway of the gene cluster mel was successfully upregulated. From the extracts of the wild-type strain, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 70 publications
(119 reference statements)
0
17
0
Order By: Relevance
“…Compared to collecting or artificially cultivating the fruiting bodies of medicinal mushrooms, mycelium fermentation offers advantages such as a stable product spectrum, shorter cultivation time, and easy industrial scale-up, making it an ideal method for researching their bioactive substances . However, compared to their natural habitat, certain activating factors are often lacking under traditional axenic conditions, resulting in some gene clusters remaining silent. , Several strategies have been applied to awaken silent genes in fungi, including genetic engineering (such as overexpression or knockout of the genes for transcription factors and global regulators), , one strain many compounds (OSMAC, mainly by altering the culture conditions), , and coculture. , Among these methods, the coculture strategy can effectively activate silent metabolic pathways by simulating natural microbial relationships, such as competition and antagonism, thus avoiding the need to manipulate the complex genome of mushrooms and reducing the workload for screening . This strategy has been well applied to explore the metabolic potential of mushrooms, leading to the discovery of many novel antimicrobial compounds, including postredienes A–F, , pleurotusin A, copsin, and 23 R -hydroxy-(20 Z ,24 R )-ergosta-4,6,8­(14),20­(22)-tetraen-3-one .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to collecting or artificially cultivating the fruiting bodies of medicinal mushrooms, mycelium fermentation offers advantages such as a stable product spectrum, shorter cultivation time, and easy industrial scale-up, making it an ideal method for researching their bioactive substances . However, compared to their natural habitat, certain activating factors are often lacking under traditional axenic conditions, resulting in some gene clusters remaining silent. , Several strategies have been applied to awaken silent genes in fungi, including genetic engineering (such as overexpression or knockout of the genes for transcription factors and global regulators), , one strain many compounds (OSMAC, mainly by altering the culture conditions), , and coculture. , Among these methods, the coculture strategy can effectively activate silent metabolic pathways by simulating natural microbial relationships, such as competition and antagonism, thus avoiding the need to manipulate the complex genome of mushrooms and reducing the workload for screening . This strategy has been well applied to explore the metabolic potential of mushrooms, leading to the discovery of many novel antimicrobial compounds, including postredienes A–F, , pleurotusin A, copsin, and 23 R -hydroxy-(20 Z ,24 R )-ergosta-4,6,8­(14),20­(22)-tetraen-3-one .…”
Section: Introductionmentioning
confidence: 99%
“…9 However, compared to their natural habitat, certain activating factors are often lacking under traditional axenic conditions, resulting in some gene clusters remaining silent. 10,11 Several strategies have been applied to awaken silent genes in fungi, including genetic engineering (such as overexpression or knockout of the genes for transcription factors and global regulators), 12,13 one strain many compounds (OSMAC, mainly by altering the culture conditions), 14,15 and coculture. 16,17 Among these methods, the coculture strategy can effectively activate silent metabolic pathways by simulating natural microbial relationships, such as competition and antagonism, thus avoiding the need to manipulate the complex genome of mushrooms and reducing the workload for screening.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These include genetic engineering, OSMAC (one strain many compounds), and coculture. 15,16 With recent rapid development of genetic tools in filamentous fungi, high expression of transcription factors and knockout of histone deacetylase genes have been widely used to broaden the structural diversity of secondary metabolites. 17,18 However, the genetic manipulation of basidiomycetes is substantially more complicated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several different strategies have been developed to activate the expression of silent genes in fungi cultured under laboratory conditions. These include genetic engineering, OSMAC (one strain many compounds), and coculture. , With recent rapid development of genetic tools in filamentous fungi, high expression of transcription factors and knockout of histone deacetylase genes have been widely used to broaden the structural diversity of secondary metabolites. , However, the genetic manipulation of basidiomycetes is substantially more complicated. Although the overexpression system or genetic editing by CRISPR-Cas9 has been established for a few basidiomycetes such as P.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we could now easily access to the sequenced genome of targeted microorganism whose metabolites have not been, or rarely, characterized. Genome-guided mining approach is usually conducted to set up the linking between secondary metabolites identification and targeted biosynthetic gene clusters (BGCs) verification [ 11 , 12 ]. Also, previous studies have demonstrated that genome mining is an effective approach that facilitated exploitation for new metabolites with fascinating structures, and numerous BGCs were investigated [ 10 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%